(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2022)
The legal framework offered by law 27.349 constitutes a good alternative to channel small and medium-sized enterprises in the jurisdiction of the province of La Pampa. The figure of the SAS has acquired a certain preponderance over other social types regulated by law 19.550. The central aspects that motivate or favor its application in commercial practice refer to the possibility of separating assets, the limitation of liability, the possibility to affect sole proprietorships, the separation of activities, and the simplification of registration and administrative procedures in its operation. Regarding the scope of the legality control carried out by the legal authority in the jurisdiction, it should be noted that it does not differ to a great extent from that which has been carried out for the other social types regulated by the LGS. The digital procedure to constitute these companies has not been implemented yet. Regarding the exercise of the autonomy of the partners’ will, and according to the professional practice, it is manifested mainly in the clauses related to the social object, the social capital and the disposition of the shares. In general, the model contract offered is adopted and adjustments are made to it in the referred clauses. Related to the risks of using the legal framework of the SAS for non-corporate purposes, it is necessary to recognize different jurisdictional realities. In any case, the accounting profession indicates its concern regarding this issue. By virtue of the above, and in order to mitigate the risks, to protect third parties, and to avoid potential corporate conflicts, it would be necessary to carry out legal and regulatory modifications in order to increase the powers of the jurisdictional control authorities, not only in the constitution but also in the operation of these companies.